Environmental Management for the Safety of Psychiatric Patients: The Challenging Role of Nurses - Areerom, Juthamas (Journal of The Royal Thai Army Nurses, 2025)
A psychiatric ward is a facility that provides overnight care for patients with mental health issues, particularly those whose symptoms may pose a risk to themselves or others. Therefore, it is essential that these wards are designed with safety for psychiatric patients. This article aims to demonstrate how environmental management is vital for the safety of psychiatric patients, helping to mitigate significant risks commonly encountered in psychiatric care. The key risks include: 1) Risk of suicide and self-harm. 2) Risk of aggressive behavior 3) Risk of escape. Managing the environment for safety is a significant and challenging role of nurses in finding crucial measures to care for and prevent potential harm to psychiatric patients.